The Impact of Leadership Practices and Internal Control Systems on Strengthening the Integrity System - Ida Rianti (Journal Research of Social Science, Economics, and Management, 2026)
Corruption remains a serious challenge in the public sector, including in Indonesia’s supreme audit institution (BPK), despite existing regulations and oversight mechanisms. This research aims to examine the influence of leadership practices and internal control systems on strengthening integrity systems. The research was conducted using a quantitative approach with survey participants, namely internal auditors at the BPK Integrity Enforcement Inspectorate, with a final sample of 32 respondents. The results of the study show that, both partially and simultaneously, leadership practices and internal control systems have a significant effect on the integrity system. The implications of these findings suggest that leadership practices and internal control mechanisms have a direct impact on the formation of a culture of transparency and accountability, oriented toward integrity values. Strong leadership and an effective, integrated internal control system can create a comprehensive governance framework to support organizational integrity. These findings provide practical guidance for public sector institutions in designing leadership development programs and strengthening internal control mechanisms to enhance integrity and prevent corruption.